Fintech Development Degree in the RA Banking System. Opportunities and Challenges - Grigoryan, Grigor («Տնտեսագետ» հրատ․)
The development of digital technologies was a great stimulus for the faster development of a number of areas. The banking sector could not be left out of all of that where the provision of traditional banking services was gradually replaced by the provision of remote digital banking services. Most of the banks operating in the world have already accepted digitization as a challenge and are taking active steps towards digitization. Newly established banks, which are trying to occupy a place in the market, mainly provide services remotely through mobile or online banking excluding the existence of a branch network. All this significantly changes the principles traditional banking services and the ways of receiving services by clients. Among digital technologies financial technology stands out which is a rapidly developing field at the intersection of financial services and advanced technologies. We can say that it is a powerful engine of technological progress which increases the global technological influence year by year. It promotes the development of innovative technologies leading to a new level of speed and flexibility in banking and the field of information technologies. In recent years the active development of fintech has also been taking place in the RA. It brings not only new opportunities but also some risks with it which we will try to reveal in this work.
Keywords: Finance